2013
DOI: 10.1111/1574-6968.12124
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the metabolic differences betweenBradyrhizobium japonicum110 bacteria and differentiated bacteroids from soybean (Glycine max) root nodules: anin vitro13C- and31P-nuclear magnetic resonance spectroscopy study

Abstract: Bradyrhizobium japonicum is a symbiotic nitrogen-fixing soil bacteria that induce root nodules formation in legume soybean (Glycine max.). Using (13)C- and (31)P-nuclear magnetic resonance (NMR) spectroscopy, we have analysed the metabolite profiles of cultivated B. japonicum cells and bacteroids isolated from soybean nodules. Our results revealed some quantitative and qualitative differences between the metabolite profiles of bacteroids and their vegetative state. This includes in bacteroids a huge accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 50 publications
(69 reference statements)
2
23
0
Order By: Relevance
“…The high mobility and the assimilation of these organic P compounds suggest that a more plastic response to P deprivation occurred with the HA treatments compared to the controls. The presence of glycerophosphodiester and phosphorylcholine were previously reported to be involved with the turnover, metabolism, and degradation of phospholipid and glycerol of P‐deprived plants ( Cheng et al, 2011; Vauclare et al, 2013). These changes in P distribution could be attributed to a modified metabolic pathway for economizing P consumption in plants and maintaining higher P concentrations in plant cells (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The high mobility and the assimilation of these organic P compounds suggest that a more plastic response to P deprivation occurred with the HA treatments compared to the controls. The presence of glycerophosphodiester and phosphorylcholine were previously reported to be involved with the turnover, metabolism, and degradation of phospholipid and glycerol of P‐deprived plants ( Cheng et al, 2011; Vauclare et al, 2013). These changes in P distribution could be attributed to a modified metabolic pathway for economizing P consumption in plants and maintaining higher P concentrations in plant cells (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…That is in agreement with previous studies that found similar AEC values for healthy nitrogen‐fixing bacteria (Upchurch and Mortenson, ). Previous NMR efforts were unable to detect these molecules in the free‐living forms (Vauclare et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In the nodule, the bacteria live as symbionts where they are able to fix nitrogen. Some strains exhibit hydrogenase activity with the soybean host and thus are more efficient in symbiotic nitrogen fixation (Maier 1981;Vauclare et al 2013).…”
Section: The Family Bradyrhizobiaceaementioning
confidence: 99%